MARRIAGE AND ITS LESSON FROM AN ISLAMIC PERSPECTIVE - Ifham Choli; Etika Nailur Rahma; Neneng Munajah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
Marriage is an effort so that humans can fulfill their needs without losing their high and noble level of humanity. Marriage also maintains the bloodline in the process of human regeneration. With marriage, kinship and people's statuses become clear. Marriage in Islam is to form a family marriage as a means to achieve happiness in life. Islam also teaches that marriage is an event that should be welcomed with gratitude and joy. Islam provides a clear concept regarding the procedures or process of a marriage that is based on the Koran and Sunnah. The research methodology used in this research is a qualitative research method with observation-based data collection techniques. The aim of this research is to find out how marriages are arranged in Islam and what the wisdom of marriage is so that a happy family, a family that is calm, peaceful and full of joy, will be created. love is based on faith and devotion to Allah SWT.